A study on cognitive and psychomotor factors of hill farmers on adoption of agri-horti farming system - CHAHAL, V P; NAIN, M S; SINGH, RASHMI; CHANDEL, S S (The Indian Journal of Agricultural Sciences, 2014)
Adoption of agri-horti system and associated factors need to be viewed in totality which calls for the empirical evidences to design pin pointed programmes in order to enhance productivity. The study conducted in Doda district of Jammu and Kashmir state revealed that the farmers’ adoption level of seed component of field crops and plant protection components of fruit crops were found to be low. Most of the respondents reported high level of training needs with respect to training and pruning, field sanitation, weed management, selection of fruit plants and diseases management. The farmers’ characteristics like family occupation, land holding, economic motivation, innovation proneness and information sources utilization were found to be positively and significantly associated with their training needs. The farmers’ preferences regarding training programme organization included one week duration, more focus on practical aspects with demonstration method and organization of training in small group in their own locality before sowing and planting season. Therefore, the study has highlighted the need for restructuring the training programmes to benefit the farmers operating agri-horti farming system. Such an approach would boost production and generate additional income for producers and other small scale operators along the value-chain.